Accurate Locations of Felt Earthquakes Using Crowdsource Detections - Bondár, István; Steed, Robert; Roch, Julien; Bossu, Rémy; Heinloo, Andres; Saul, Joachim; Strollo, Angelo (Frontiers in Earth Science, 2020)
We present a methodology that uses crowdsource detections as an initial location to obtain fast and reliable hypocenter parameters of felt earthquakes using arrival-time data from the GEOFON Program. We derive selection criteria using a 3-year-long training set from the trial runs at the European-Mediterranean Seismological Centre (EMSC) to identify accurate event locations at a high confidence level. Since an event may have several crowd-sourced detections, we also develop a methodology dealing with multiple triggers. We validate the selection criteria using real-time processing of recent data and demonstrate that 95% of the selected events are within 50 km distance from the traditional seismic location published by the EMSC. We show that our methodology provides accurate locations much faster than those published by conventional seismic methods. On average, the EMSC CsLoc service can provide rapid and accurate locations within a minute after the occurrence of a felt earthquake.